STRUCTURAL BEHAVIOR OF METAKAOLIN INFUSED CONCRETE STRUCTURE (Nigerian Journal of Technology, 2017)
This work researched into the use of metakaolin as a partial substitute for cement in concrete, metakaolin was obtained by the calcination of kaolin clay to about 700 0C Cement was replaced with the metakaolin at 0, 5, 10, 15, 20, 25, 30, and 35% at water cement ratio of 0.5. Tests such as chemical analysis, compressive strength, flexural or modulus of rupture and bond strength were carried out on the concrete samples. Chemical analysis results showed that the metakaolin is a class “N” pozzolan, while the mechanical test showed that the strength of concrete increased from 5% to 20% replacement, and the strength peaked at 20%, but decreased above this value; concrete made with metakaolin performed better than the control sample at all the percentage replacements used in this work. http://dx.doi.org/10.4314/njt.v36i2.2